Magma Degassing and Gold Mineralization in the Alkaline Intrusion- Hosted Gilt Edge Gold Deposit,Northern Black Hills, South Dakota, USA - Groff, John A. (Earth and Planetary Science, 2024)
Gold mineralization in the Gilt Edge  deposit was closely associated with magmatic differentiation and the formation of a Tertiary alkaline intrusive complex within the Lead–Deadwood dome.. Fluid inclusions and trace element geochemistry were used to study fluid evolution and determine sources. Quartz disseminated in unaltered trachyte porphyry  hosts two populations of primary inclusions: 1) hypersaline i S–L–V  a red hematite crystal and 2) mixtures of L–V and V– L  that record phase separation at ~700oC. Whereas samples of hydrothermal quartz collected from in ore zones within and beyond structures (e.g., fault and breccia zones) contain dominant populations of V–L and L–V inclusions, respectively. Mineralization in structures formed from complex fluids of magmatic origin based on inclusions containing five transparent salt crystals and opaque crystals with cubic and round habits that have homogenization temperatures (Th)  650oC and salinities  63 wt.% NaCl equiv. In contrast, broader areas of disseminated mineralization in argillized and propylitized rocks contain hydrothermal quartz hosting large populations of L–V inclusions with Th of 200o360oC and salinities of 10–30 wt.% NaCl equiv., which reflect fluid mixing.  Trace element concentrations are significantly higher in samples from structures and define zones of near surface Ag–As–Zn–Pb and deep Au–W–Mo–Cu. Whereas low trace element concentrations characterize propylitized quartz trachyte porphyry, except for high concentrations of Sb and Hg that occur at depth and likely track the retreat of isotherms as the hydrothermal system collapsed. These data show that during differentiation in a deep magma chamber, volatile-rich low-density fluids were periodically degassed into preexisting structures that were reactivated. Gold deposition during four stages of mineralization likely occurred due to boiling, changes in oxygen fugacity, and fluid mixing. ER